Application of Biochar and Poschar from Several Types of Animal Manure on the Growth and Yield of Red Chili Plants (Capsicum annuum L.) - Yohanes Parlindungan Situmeang; Made Suarta; Afelinus Rematwa (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2022)
This study aims to determine the effect of doses of biochar and various types of poschar and their interactions on the growth and yield of red chili plants. This research was conducted in Buduk village, Mengwi sub-district, Badung district at an altitude of 65 meters above sea level. This research activity took place from April to July 2021. The design used in this study was a factorial randomized block design (RBD) consisting of 2 treatment factors. The first factor is the dose of biochar (B) which consists of 2 levels (0 and 15 tons/ha), while the second factor is the type of poschar (P) which consists of 3 levels (without poschar, beef poschar, and goat poschar). The results showed that the interaction between the dose of biochar and the type of poschar (BxP) had a significant effect on the number of leaves and fruit number, fruit weight and had a very significant effect on stem diameter, but had no significant effect on plant height, number of productive branches, fruit length, and diameter. fruit per plant. Biochar treatment had a very significant effect on the variables of plant height, number of leaves, and fruit weight per plant and significantly affected the number of fruits, number of productive branches per plant, and fruit length per plant but had no significant effect on stem diameter. Poschar application showed no significant effect on all observed variables except for plant height which had a significant effect. The highest fresh weight of chili fruit per plant was obtained from the interaction of chicken biochar with no poschar, which was 1326.20 g, followed by the interaction between chicken biochar and goat's poschar, which was 1297.85 g, and the interaction between chicken biochar and beef poschar, which was 1081.71 g which increased by 114.11%, 109.53%, and 74.64% respectively compared to the interaction between the treatment without biochar and without poschar which was 619.41 g.